ANALISIS PROFIL KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS VIII SMP DI SURABAYA BERDASARKAN INDIKATOR ENNIS 2011 - Shofa Imamy, Halwa; Nurul Hidayati, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the critical thinking skill profiles of eighth-grade students at SMP 2 Surabaya based on Ennis’s critical thinking indicators. The study employed a descriptive quantitative approach involving 33 students. The research instrument consisted of a critical thinking skills test comprising 15 multiple-choice items developed based on five indicators: elementary clarification, basic support, inference, advanced clarification, and strategy and tactic. Data analysis was conducted descriptively using mean scores and standard deviations to describe the students’ critical thinking skills achievement. The results of the study indicate that students’ critical thinking skills fall into the moderate-to-low category, with indicator achievement percentages ranging from 45.33% to 50.67%. The elementary clarification and basic support indicators achieved the highest percentage at 50.67%, while the inference and advanced clarification indicators showed the lowest achievement at 45.33%. Analysis by gender indicated that the average scores of male (M = 7,50) students were slightly higher than those of female students (M = 7,16), though this did not show a statistically significant difference. These findings indicate that students are relatively more capable of understanding and explaining information compared to engaging in deep inferential reasoning and evaluating assumptions. This study can serve as a foundation for developing instruction that systematically trains analytical skills, evidence-based argumentation, and reflection to enhance critical thinking skills in a sustainable manner